Analisis Yuridis Tentang Pembuktian Dakwaan Dengan Saksi-Saksi Yang Dibacakan Oleh Penuntut Umum Dalam Pemeriksaan Perkara Penggelapan Dalam Jabatan - Yuni Widayanti (Verstek, 2017)
The case of embezzlement with the dependent Bagus Pritono Aji do abuse of the authority to do billing money to Hengki Hendra as the owner of the shop Jumbo Digital with the use of an invoice made UD.Denka Elektrindo. Without permission from other people, the money used for the sake of personal defendants. Central Jakarta Court dropped the felony to the decided to sent the defendant to jail for 1 (one) year .       The results of the research show that in the process of proving the charges, the Prosecutor can't present witnesses so the judge asked the Prosecutor to read from the witness discription. To prove the allegations by witnesses that was read by the prosecutor on a case of embezzlement in the department is not in accordance with the terms of the Criminal Procedure Code, because according to the terms of Article 185 paragraph (1) of the Criminal Procedure Code mentioned that witnesses as a means of evidence is what the witness stated in court. Witnesses is carried out by the public prosecutor considered by the Judge with the stipulation that the witnesses-the witness has conformity with the statements of the accused as well as the device evidence the invoice billing. The testimony was read by a prosecutor that in this case the judge also come under consideration because it can be made a tool of evidence clues that can lead to the conviction of a judge in a cut scene in accordance with Article 183 of the Criminal Procedure Code.        Key words : Embezzlement for practicing, Evidence, Witness